Convergent synthesis of 4, 5-branched inner-core oligosaccharides of lipopoly- and lipooligosaccharides. Issue 12 (2nd December 2015) - Yi, Ruiqin; Narimoto, Hirofumi; Nozoe, Miku; Ichiyanagi, Tsuyoshi
Abstract: The convergent synthesis of branched inner-core oligosaccharides of lipopoly- and lipooligosaccharide with a 3-deoxy-d - manno -oct-2-ulosonic acid (Kdo) disaccharide acceptor was achieved. The l - glycero -d - manno -heptopyranose (Hep) units for the branched core oligosaccharide Galβ(1-4)Glcβ(1-4)Hep and Hepα(1-3)Hep were prepared from the corresponding Hep building blocks. To obtain 4, 5-branched core oligosaccharide structures, the common acceptor Kdoα(2-4)Kdo was glycosylated with the Hep units. Graphical abstract: : Convergent synthesis of branched inner-core oligosaccharides of LPS/LOS.